Power Consumption of Parallel Programming Interfaces in Multicore Architectures: A Case Study - Garcia, Adriano Marques; Schepke, Claudio; Girardi, Alessandro Gonçalves; da Silva, Sherlon Almeida (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
This paper evaluates the power consumption of different parallel programming interfaces (PPI) in a multicore architecture. These PPIs are: PThreads, OpenMP, MPI-1 and MPI-2 (spawn). We measure the total energy and execution time of 11 applications in a single architecture, varying the number of threads/processes. The goal is to show that these applications can be used as a parallel benchmark to evaluate the power consumption of different PPIs. The results show that PThreads has the lowest power consumption among the interfaces, consuming less than the sequential version for memory-bound applications.